al-Ta‘līm al-‘Arabī fī Nījīriyā: Bayna Mu’āmarāt al-Tadmīr wa-Majhūdāt al-Ta‘mīr - Salih Muhammad Jum'ah-Alaso (Al-Ma‘rifah, 2019)
The Arabic language in the Nigerian society is of paramount importance as the language of religion, history, culture, economy, politics, international relations, and others. The current researcher focused his attention on the growth of the Arabic language and its development in Nigeria since its entry and the recognition and respect and progress in the times of the Islamic Caliphate in Sokoto, and ignored the contempt and contempt and delay in the days of British colonial, and then the love, attention, and development of the Arab scientists Nigerian Her enthusiasts. The researcher approached the historical recovery method by retrieving the past of the Arabic language in these countries and their effects. In gathering information, the researcher used the interview and the electronic inquiry method with or without yes, especially when talking about the problems facing Arab education in Nigeria. The findings of the researcher include the following: (1) Arabic is the first language of civilization seen by the Nigerian people and educated by the culture of writing and reading at a time when the two were a kind of magic and mastered by very few people in society. (2) Nigerian Muslims are very interested in Arab education and have spent every Gal and Nafis to develop it from the first era to the present. The research concluded with some suggestions and recommendations towards the development of Arab education in Nigeria.